А Сritiсаl Pеriоd fоr Асquiring а Sесоnd Еnglish Lаnguаgе - Dаdаbоеvа D.О. (Scientific Trends, 2024)
Children learn language more easily than adults, although when and why this ability declines remains unclear for both empirical reasons (insufficient research) and conceptual reasons (I am confident that students who begin learning at different ages cannot independently itself to identify changes in basic learning abilities). We address both limitations with a dataset of unprecedented size (669,498 native and non-native English speakers) and a computational model that estimates the underlying movement trajectory. Develop ability by separating current age, age of first contact, and years of experience. This leads us to take the first direction, and he, like the graph, and discovers that this is what he is. DESLINES StefeDILU. This conclusion is true not only for “difficult” syntactic phenomena, but also for “easy” syntactic phenomena, which are usually mastered in the early stages of development. The results support the existence of a well-defined critical period for language acquisition, but the age of shift occurs much later than previously thought. The size of the data set also provides new insight into several other unresolved questions in language acquisition.
Keywords: Lаnguаgе асquisitiоn; Сritiсаl pеriоd; L2 асquisitiоn